Decolorization of Methylene Blue Solution by Electrocoagulation Using Aluminum Electrodes - ,Waraporn Pantorlao (Science Faculty of Chiang Mai University, 2019)
In the present work, the electrocoagulation process and its performance of dye removal using aluminium as electrodes were investigated. Methylene blue solution was used as synthetic dye wastewater for dye removal efficiency. The optimal condition of electrocoagulation operation for dye removal was examined including current density (10-30 mA/cm2), concentration of NaCl (1.5-6.0 g/L) and electrolysis time (2-15 min). The efficiency of dye removal was evaluated by the absorbance of the methylene blue solution at 664 nm. The results showed that the increasing current density from 10 to 30 mA/cm2 enhanced the dye removal efficiency to 88%. The high NaCl concentration of 6 g/L with the electrolysis time of 10 minute provided the dye removal efficiency approximately 92%. In addition, the 15 min of electrolysis time provided the slightly higher efficiency with 93%. However, it has to be noted that with increasing the electrolysis time and current density caused high formation of sludge that can prevent the interaction of electrocoagulation process and increase the use of energy consumption.